Staging esophageal cancer: low EUS accuracy in t2n0 patients - de Nucci, Germana; Petrone, Maria Chiara; Imperatore, Nicola; Asti, Emanuele; Rossi, Gemma; Manes, Giampiero; Vecchi, Maurizio; Pastorelli, Luca; Bonavina, Luigi; Arcidiacono, Paolo Giorgio (Endoscopy International Open, 2021)
Background and study aims Esophageal cancer (EC) is one of the most lethal malignancies worldwide. Staging of EC is performed with computed tomography (CT), positron-emission tomography (PET), and endoscopic ultrasonography (EUS). Patient management mostly depends on lymph node status. Compared to histopathology, the accuracy of EUS for T and N parameters is about 85 % and 75 %, respectively. Errors in staging may change prognosis. The aim of this study was to assess the role of EUS in T2-N0 EC considering the experience of two high-volume digestive endoscopic centers.Methods Two prospectively collected databases were queried to identify all patients with EC, staged as cT2N0 by EUS, with no distant metastases at CT/PET scan and who underwent transthoracic esophagectomy. Preoperative EUS staging (cTNM) was compared to histopathology of the surgical specimen (pTNM) to evaluate accuracy.Results Of 729 consecutive patients with EC between January 2011 and September 2018, 72 (49 men) had cT2N0 disease. CT and PET scans confirmed the absence of distant metastasis. In 43 of 72 patients (60 %), the evaluation was correct, 23 of 72 (31,7 %) were understaged, and six of 72 patients (8,3 %) were overstaged. Among the understaged patients, eight were understaged by tumor depth (35 %), seven by nodal involvement (30 %), and eight by both (35 %). All six patients who were overstaged had T1b-N0 disease. EUS accuracy was 77 % in staging for tumor depth and 82 % in staging for nodal metastases. The positive predictive value (PPV) for cT2N0 EC was 60 % (43 pT2N0 /72 cT2N).Conclusions The accuracy of EUS staging of T2N0 EC is low, with only 60 % of patients undergoing appropriate therapy based on histopathology.